1984
DOI: 10.1143/jjap.23.l391
|View full text |Cite
|
Sign up to set email alerts
|

Local Loading Effect in Selective Silicon Epitaxy

Abstract: In selective epitaxy, growth rate is modified by the ratio of unmasked area to entire surface area and by each window area on a wafer. Such “local loading effect” phenomena were studied in a SiH2Cl2/HCl/H2 selective epitaxial growth system. The effect is attributed to species spatial concentration variation which is generated by coexistence of a masked area and windows on a wafer. The growth condition which can suppress the effect is obtained for VLSI device fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…These trends are related to the selective nature of the deposition and have also been reported in the past from selective silicon epitaxy. 12 However, for this process it has also been shown that some control of loading effects and pattern dependency can be achieved by adjusting the partial pressure of HCl. 13,14 A CVD deposition on blanket wafers may be described using the classical boundary layer theory.…”
Section: Resultsmentioning
confidence: 99%
“…These trends are related to the selective nature of the deposition and have also been reported in the past from selective silicon epitaxy. 12 However, for this process it has also been shown that some control of loading effects and pattern dependency can be achieved by adjusting the partial pressure of HCl. 13,14 A CVD deposition on blanket wafers may be described using the classical boundary layer theory.…”
Section: Resultsmentioning
confidence: 99%
“…We observe polycrystalline SiGe deposits on masked regions, although epitaxial material is selectively deposited on the exposed substrates. The polycrystalline deposits actually simplify the growth issue to some extent as loading effects [9] are greatly reduced. In our study, we utilized many different characterization techniques to monitor the structural integrity of Ge/Si SEG films.…”
Section: Results From Grant Daah04-96-1 -0364mentioning
confidence: 99%
“…As studied by Ishitani et al, 10 the addition of HCl during epitaxial growth shifts the chemical system to a more reactive controlled region by reducing the supersaturation of the Si species, thus minimizing the loading effect. As studied by Ishitani et al, 10 the addition of HCl during epitaxial growth shifts the chemical system to a more reactive controlled region by reducing the supersaturation of the Si species, thus minimizing the loading effect.…”
Section: Resultsmentioning
confidence: 99%